Addressing Education, Training, and Employment Supports for Prisoners With Cognitive Disability: Insights from an Australian Programme. Issue 1 (20th August 2019) - Rowe, Simone; Dowse, Leanne; Newton, Danielle; McGillivray, Jane; Baldry, Eileen
Abstract: The provision of appropriate education, training, and employment supports for incarcerated people is pivotal to mitigating the risk of recidivism, to improving rehabilitative outcomes, and to securing employment upon release. People with cognitive disability are disproportionately represented in prisons internationally. The vast majority of this group have significantly low levels of education, are unable to participate meaningfully in mainstream prison programs, are more likely to return to prison than their nondisabled peers and are generally excluded from the labor market. There is thus a significant need for specialized in‐prison education, training, and employment programs for this group. However, in Australia and internationally such programs are scant. There is also very little known about good policy and practice in this domain. We present findings from qualitative research conducted on one of the few specialist education, training, and employment program models for prisoners with cognitive disability in Australia. The findings suggest that a practice model informed by and delivered from a well‐considered theoretical base by a collaborative multidisciplinary team capable of adapting mainstream education, training, and employment programs in a flexible and culturally sensitive manner offers an opportunity to provide improved outcomes and greater equity for this highly disadvantaged group. The implications for policy and practice in this domain are discussed. We conclude that the expansion of appropriately designed education, training, and employment programs for prisoners with cognitive disability is critical to protecting the human rights and improving the life trajectories of this highly disadvantaged group.